Diseño de un sistema de costos por procesos en la empresa SIEM, ubicada en San José de Pichaló, perteneciente al cantón Latacunga, provincia de Cotopaxi. - Carrera Cevallos, Cindy Carolina (2019)
The purpose of this paper is to improve the deficient control of accounting records, especially the determination of the cost elements and thus having a better management of the economic resources. For this reason, the objective of this integrating project is to design a cost system for the efficient management and control of the economic resources of the company, in this way improving administrative and financial management. In order to fulfill this purpose, methods such as bibliographic and documentary compilation were used; techniques such as the application of interviews to the person in charge of the production department and the observation guide, which was carried out directly in "SIEM", all with the objective of collecting primary information for the achievement of the cost system. Through the situational diagnosis, a clearer idea of the problem in question was obtained. In addition, the competences related to the professional field and the scientific-technical foundation are described, the same ones that contributed in the achievement of the present project. At the end of the project it was determined that currently the price obtained in the sale of the product only covers the payment of the raw material and the difference for direct labor and in some cases no profit is generated, due to the way empirical as your costs are determined. As a result of the present research work, it's proposed to increase all the costs involved in the technical elaboration at an average sale Price of $ 1.00 per hygienic paper, obtaining an ideal profit of $ 0.25 equivalent to 33% per unit, what percentage means an increase of income and therefore of the utility.